Measuring student debt and its performance - Meta Brown; Andrew Haughwout; Donghoon Lee; Joelle Scally; Wilbert van der Klaauw (Federal Reserve Bank of New York, 2014)
Studies continue to indicate that higher education is frequently a worthwhile investment for individuals and that it raises the productivity of the workforce as a whole. While the rising cost of post-secondary education has not eliminated this "college premium", it has raised new questions about how growing numbers of students can make these investments. One solution to this problem is student loans, which have come to play an increasingly important role in financing higher education. Yet, despite its importance, educational debt is not well understood. Among the reasons is that there exist few central repositories of information on the characteristics and performance of all student loans, which currently include loans made by both government and private lenders. In this paper, we bring a new data set to bear on this important issue and present a brief analysis of the historical and current levels of student debt and how those loans are performing. We also briefly discuss the implications of student loans for borrowers and the economy.
Keywords: D12; I22; D14; 330; student debt; household debt